Pelestarian Tari Andun pada Masyarakat Bengkulu Selatan - Sella Tri Komala; Supriyanti Supriyanti; Rina Martiara (Institut Seni Indonesia Yogyakarta, 2020)
Preservation of Andun Dance in South Bengkulu. Andun dance is one of the dances of South Bengkulu’s people, which is currently less popular. This dance is a form of cultural and traditional art in South Bengkulu that still exists and has Islam and traditional nuance. In a marriage ceremony, for example, this dance is performed for seven days and seven nights. For those with a modern view, the Andun dance is a series of long and tiring processions and should be abandoned or modified. However, because it has become a custom and tradition, most people still carry out this long procession until now, even though it requires a lot of time and money. Andun dance is now less attractive because there are so many foreign cultures that enter South Bengkulu people, especially its young people. Andun dance is also getting worse because the places to express this dance are decreasing in number. For example, South Bengkulu people’s traditional marriage rituals are usually held for seven days and seven nights. Still, at present, the practices held are not carried out that long. Andun dance, which is currently experiencing ups and downs, has not been able to regrow the community’s interest and youth. This research focuses on how the efforts to preserve the Andun Dance in the people of South Bengkulu. One of the efforts made by the government is to carry out the Andun dance festival. In several leading schools, Andun dance is taught as extracurricular activities. The efforts made by the community regarding the preservation of the Andun dance are deliberating so that the Andun dance can be performed by the middle to lower class communities. Besides, artists also carry out preservation efforts by providing guidance or training for Andun dance to their students.Keywords: preservation; Andun dance; South Bengkulu